OSA Wellness Scale (OWS): A New Health-Related Quality of Life Test in Obstructive Sleep Apnea Patients Treated with Mandibular Advancement Device - Domenico Ciavarella; Alessandra Campobasso; Laura Guida; Angela Pia Cazzolla; Graziano Montaruli; Fabrizio Corlianò; Luigi Romano; Michele Cassano; Michele Tepedino; Giuseppe Burlon (Hindawi Limited, 2022)
Objectives. To present a new short self-test, called the OSA wellness scale (OWS), for assessing the health-related quality of life (HRQoL) changes in obstructive apnea syndrome (OSA) patients treated with mandibular advancement device (MAD). Methods. 51 OSA patients (8 women and 43 men, mean age 52.3) treated with a fully customizable MAD device (Protrusor) were retrospectively enrolled. Each patient received a home sleep apnea testing (HSAT) at baseline (T0) and after three months of MAD treatment (T1). Two self-test evaluations, the Epworth sleepiness scale (ESS), and OWS were also submitted at T0 and T1. The OWS was a short self-test of 8 questions for evaluating the daytime HRQoL. Patients gave an assessment from 0 to 3 for each question. At the end of the questionnaire, the patients had a score from 0 to 24, resulting from the sum of all 8 scores. The higher the score, the greater the patient's perceived state of discomfort. Results. At T1, a significant decrease in the oxygen desaturation index (ODI) and apnea-hypopnea index (AHI) was shown (p<0.0001), while no significant changes in body mass index (BMI) were found. Both the ESS and the OWS records showed a significant reduction in daytime sleepiness and HRQoL (p<0.0001). Conclusion. The OWS could be a useful method to verify and numerically compare the perceived quality of life in OSA patients, before and after MAD therapy.